2022
DOI: 10.1029/2021jb023141
|View full text |Cite
|
Sign up to set email alerts
|

Review: Induced Seismicity During Geoenergy Development—A Hydromechanical Perspective

Abstract: The basic triggering mechanism underlying induced seismicity traces back to the mid‐1960s that relied on the process of pore‐fluid pressure diffusion. The last decade has experienced a renaissance of induced seismicity research and data proliferation. An unprecedent opportunity is presented to us to synthesize the robust growth in knowledge. The objective of this article is to provide a concise review of the triggering mechanisms of induced earthquakes with a focus on hydro‐mechanical processes. Four mechanism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 242 publications
0
12
0
Order By: Relevance
“…Fractures occur ubiquitously in the earth's crust at multiple scales spanning from microscopic to continental, due to tectonic process, lithostatic stress, geothermal loading, or geofluid pressure. These fractures play a crucial role in subsurface substance migration, and their transport properties are thus relevant to many natural geophysical processes and engineering activities, such as mineral precipitation, carbon and nitrogen cycling, induced seismic activity, groundwater contamination remediation, and oil/gas resource and geothermal energy for exploitation (Bhattacharya & Viesca, 2019; Birdsell et al., 2015; Ge & Saar, 2022; Hyman et al., 2019; Jones & Detwiler, 2019; Kang et al., 2015; Lee et al., 2017; Vasseur & Wadsworth, 2019; Wang et al., 2020; Zheng et al., 2019). Due to geometric heterogeneity of rock fracture and complexity of flow regime (Lee et al., 2015; Stoll et al., 2019), it is not easy to characterize solute transport in rock fractures, let alone predict this process.…”
Section: Introductionmentioning
confidence: 99%
“…Fractures occur ubiquitously in the earth's crust at multiple scales spanning from microscopic to continental, due to tectonic process, lithostatic stress, geothermal loading, or geofluid pressure. These fractures play a crucial role in subsurface substance migration, and their transport properties are thus relevant to many natural geophysical processes and engineering activities, such as mineral precipitation, carbon and nitrogen cycling, induced seismic activity, groundwater contamination remediation, and oil/gas resource and geothermal energy for exploitation (Bhattacharya & Viesca, 2019; Birdsell et al., 2015; Ge & Saar, 2022; Hyman et al., 2019; Jones & Detwiler, 2019; Kang et al., 2015; Lee et al., 2017; Vasseur & Wadsworth, 2019; Wang et al., 2020; Zheng et al., 2019). Due to geometric heterogeneity of rock fracture and complexity of flow regime (Lee et al., 2015; Stoll et al., 2019), it is not easy to characterize solute transport in rock fractures, let alone predict this process.…”
Section: Introductionmentioning
confidence: 99%
“…As the scenario in Figure 8 b shows, the dense isoline area of the groundwater head was distributed around the boundary of coal mining claims and was difficult to extend outward. Therefore, it was beneficial to the geological storage of mine water in the basin-scale for the Ordos basin, but the renaissance of induced seismicity should be avoided [ 73 ]. The high frequency of water injection often induced the seismic activities around wells and was analogous to faults re-activation seismic in the gas extraction [ 74 ].…”
Section: Resultsmentioning
confidence: 99%
“…Field and modeling studies have suggested that pore pressure diffusion (e.g., Hornbach et al., 2015; Hsieh & Bredehoeft, 1981; Keranen et al., 2014; Nakai, Weingarten, et al., 2017), poroelastic stress changes (e.g., Goebel et al., 2017; Segall & Lu, 2015; Zhai et al., 2019), and static stress changes (e.g., Brown & Ge, 2018), including that from aseismic slip (e.g., Guglielmi et al., 2015), all contribute to inducing seismicity. The relative significance of these mechanisms varies at different stages of the seismic sequence and for seismicity at difference distances from injection, but pore pressure is considered a primary trigger for initiating induced seismicity sequences (Chang & Segall, 2016; Ge & Saar, 2022; Segall & Lu, 2015). This study focuses on early‐stage seismicity and the contribution of pore pressure changes.…”
Section: Introductionmentioning
confidence: 99%